The dynamics of urbanization, land use land cover changes, and land expropriation in Addis Ababa, Ethiopia - Ayenachew, Yeshitla Agonafir; Abebe, Birhanu Girma (Frontiers in Environmental Science, 2024)
Over the past two decades, Addis Ababa has witnessed a relentless transformation in its land use and land cover. Primarily driven by the conversion of agricultural land through extensive expropriation in the city's expansion areas. The study explores the dynamic land use land cover changes and associated land expropriations from peri-urban farmers in the rapidly growing Addis Ababa, Ethiopia. The study utilized a time series of global land cover and land-use change datasets (GLAD) covering the years 2000 to 2020. Moreover, empirical data is gathered through a household survey conducted among 349 systematically selected expropriated farmers across four sub-cities of Addis Ababa. The findings underscore a profound shift in the city's land use and land cover over the past two decades. The built-up area emerges as the predominant land cover, witnessing a substantial increase of 25.28% (13,150.30 hectares) over the past two decades. Concurrently, agricultural land and vegetation cover decreased by 15.92% and 9.35%, respectively, indicating a significant outward expansion of the city. This expansive growth, driven by the city's rapid development, has resulted in extensive land expropriations primarily affecting peri-urban farmers. The expropriations were mainly for housing, investment, industrial parks, and infrastructure development. Thus, we urge the city administration to carefully manage the horizontal expansion of built-up areas at the expense of the agricultural land and vegetation cover. Finally, we recommend holistic and sustainable development strategies, developed collaboratively with local communities and planners, to safeguard the long-term well-being of city residents.